214k views
0 votes
Simplify cot(t)/csc(t)-sin(t)

1 Answer

6 votes

ANSWER

= sec(t)

Step-by-step explanation

First let's rewrite this in terms of sines and cosines:


(\cot t)/(\csc t-\sin t)

The cotangent is the reciprocal of the tangent:


\cot t=(1)/(\tan t)=(\cos t)/(\sin t)

And the cosecant is the reciprocal of the sine:


\csc t=(1)/(\sin t)

Replace into the given expression:


(\cot t)/(\csc t-\sin t)=((\cos t)/(\sin t))/((1)/(\sin t)-\sin t)

We can add the two terms in the denominator:


((\cos t)/(\sin t))/((1)/(\sin t)-\sin t)=((\cos t)/(\sin t))/((1-\sin ^2t)/(\sin t))

The denominators of each fraction get cancelled out:


((\cos t)/(\sin t))/((1-\sin^2t)/(\sin t))=(\cos t)/(1-\sin ^2t)

We still can simplify this a little further. Remember the identity:


\cos ^2t+\sin ^2t=1

If we solve it for cos²t:


\cos ^2t=1-\sin ^2t

We have the same expression of the denominator. So let's replace the denominator by cos²t:


(\cos t)/(1-\sin^2t)=(\cos t)/(\cos ^2t)

Simplify the square:


(\cos t)/(\cos^2t)=(1)/(\cos t)

And this is the secant of t:


(1)/(\cos t)=\sec t

User Ak Sacha
by
5.2k points